Educational objectives and national assessment - Butterfield, Sue (Assessing assessment, 1995)
Changes in assessment are at the heart of government policy for change in the UK. The GCSE, the National Curriculum and National Vocational Qualifications seek to make the progress of individuals more measurable - in order to make education professionals more accountable. These changes create a precarious balance - between the promise of better opportunity for students and a system of centralized control which could be stifling for teachers and learners alike. This book takes an overall view of the technical claims made for improvements in assessment, alongside the policy agenda within which the changes are introduced. It highlights the dangers of taking a fragmented view - and allowing a competitive system and league tables to be based on information which may be technically shaky